Business Development Efforts and Financial Plan: Lakso Sriwijaya - Rita Martini; M. Thoyib; Periansya Periansya (Institute for Research and Community Services, 2018)
The present community service program aims to provide understanding and assistance in product development and business finance plan. The target audience of this program is Lakso Sriwijaya. The activity ranges from providing information on developing a long-term practical and durable lakso business to providing assistance in developing the business finance plan. Accounting information is a tool used by users of accounting information for decision making, especially business people. The training given resulted in enhanced professionalism and better business management. Management that focuses on development in business financial planning tends to generate more statutory accounting information, budget and additional income from its business.